2017
DOI: 10.5946/ce.2017.167
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Pancreatic Neuroendocrine Tumors: Fine Needle Intervention including Ethanol and Radiofrequency Ablation

Abstract: Pancreatic neuroendocrine tumors (PNETs) are increasingly being detected, though usually as incidental findings. Majority of the PNETs are non-functional and surgical resection is the standard of care for most of them. However, in patients with small PNETs localized within the pancreas, who are unfit or unwilling for surgery, alternate methods of treatment are needed. Direct methods of ablation of PNETs, using either ethanol injection or radiofrequency ablation (RFA), are emerging as effective methods. The lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Previous reports on treatment with EUS-guided ethanol injection have described the amount of ethanol as ranging from 0.3 to 8.0 mL. [3][4][5][6][7] Park et al 3 reported the outcomes of 11 patients with 14 tumors, and a median 1.6 (range: 0.5-3.8) mL of ethanol per session was used for tumors of a median 12.2 (range 8-19) mm in size. Median total amount of ethanol for each tumor was thus 2.5 (range 0.5-7) mL.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous reports on treatment with EUS-guided ethanol injection have described the amount of ethanol as ranging from 0.3 to 8.0 mL. [3][4][5][6][7] Park et al 3 reported the outcomes of 11 patients with 14 tumors, and a median 1.6 (range: 0.5-3.8) mL of ethanol per session was used for tumors of a median 12.2 (range 8-19) mm in size. Median total amount of ethanol for each tumor was thus 2.5 (range 0.5-7) mL.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal approach for treating patients with nonfunctional, small (≤2 cm in diameter) pancreatic neuroendocrine tumors (p‐NET) is controversial . Recently, endoscopic ultrasonography (EUS)‐guided ablation has been proposed for the treatment of patients with small p‐NET . Using a pure ethanol or ethanol‐lipiodol emulsion, the complete ablation rate has been reported to be approximately 50% with a single session and up to 60% with an additional session .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations